2023
DOI: 10.1007/s10639-023-11615-w
|View full text |Cite
|
Sign up to set email alerts
|

Learner autonomy, learner engagement and learner satisfaction in text-based and multimodal computer mediated writing environments

Abstract: Technology creates variant learning experiences which are context specific. This study examined the comparative potential of multimodal and text-based Computer Mediated Communication (CMC) in fostering learner autonomy, learner engagement and learner e-satisfaction as well as learner writing quality. To this end, 40 Iranian male and female EFL (English as foreign language) students were selected on the basis of their writing proficiency and were randomly assigned into text-based and multimodal CMC research gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Consequently, it is reasonable to assume that engagement in IDLE may lead to greater online course satisfaction among EFL students. Indeed, studies have shown that autonomy can positively impact learners’ sense of satisfaction in online environments ( Mohammadi Zenouzagh et al, 2023 ). Furthermore, IDLE activities can foster the development of learners’ social skills through increased interaction opportunities with others on interactive platforms, potentially boosting online course satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is reasonable to assume that engagement in IDLE may lead to greater online course satisfaction among EFL students. Indeed, studies have shown that autonomy can positively impact learners’ sense of satisfaction in online environments ( Mohammadi Zenouzagh et al, 2023 ). Furthermore, IDLE activities can foster the development of learners’ social skills through increased interaction opportunities with others on interactive platforms, potentially boosting online course satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Islamic education teachers face several challenges in implementing the Merdeka Curriculum. First, the challenge faced is teacher competence (Hadi et al, 2023;Jones et al, 2021;Mahmud et al, 2023;Mohammadi Zenouzagh et al, 2023). Merdeka Curriculum requires teachers to have a deep understanding of the subject and the ability to develop innovative learning materials and methods (Looi et al, 2023).…”
Section: Challenges Faced By Islamic Education Teachers In Implementi...mentioning
confidence: 99%
“…Therefore, using wiki can potentially reduce the learning costs of students to engage in the focal learning activities, thus increasing their sense of autonomy, convenience, and perceived flexibility (Barajas & Frossard, 2018). Wiki may encourage students actively engage in collaborative learning activities and jointly take responsibility for learning (Bizami et al, 2023;Mohammadi Zenouzagh et al, 2023). Thus, this study suggests that similar PBL activities can take advantage of the functions of wiki platforms (e.g., coauthoring and the tracking and recording functions of the coauthoring process) to customize their learning content and to better support students' learning processes (e.g., capturing information about PBL 1 3 cases, creating organized knowledgebase, facilitating student collaboration to synthesize critical learning issues of PBL cases, and developing communication skills) in order to improve their learning performance.…”
Section: Implications For Education Practicementioning
confidence: 99%
“…Previous studies state that an appropriate collaborative digital platform can improve the flexibility, mobility, interactions, and quality of logical reasoning of learning activities that contribute to the enhancement of students' learning performance (Bringula & Atienza, 2022;Mohammadi Zenouzagh et al, 2023). Students can access various viewpoints/opinions and learning resources, which are vital for performing deep learning activities (Stockleben et al, 2017;Resta & Laferrière, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation